Use of cyclohexane in analysis by steric exclusion chromatography - Bonfils F; Achi A K; Laigneau J C; Sainte-Beuve J (Rev G. Caou. Plast, 1995)
Cyclohexane was used as the elution solvent in steric exclusion chromatography (GPC) studies of the molecular weight and MWD of different NR samples. It was possible to determine the influence of various phenomena such as atmospheric UV and drying conditions on MW and MWD. The use of cyclohexane avoided blocking of the columns, a problem often encountered when using other solvents such as THF.
Source Year: 1996